Efektivitas Tumpangsari Kunyit terhadap Penekanan Nematoda Sista Kuning pada Kentang - Dini Munawaroh; Subagiya Subagiya; Susilo Hambeg Poromarto (Agrosains : Jurnal Penelitian Agronomi, 2019)
Golden cyst nematode is one of the important pests that causes potatoes loss yield. Globodera rostochiensis is the pest that difficult to control because it can withstand in adverse environmental conditions. In Indonesia, golden cyst nematode was first discovered in 2003 in East Java. One of the methods that used in this research is intercropping system. The main objectives in this study was to examine how the effect of turmeric plants on intercropping system to cysts population and amount of eggs on golden cyst nematode and the use of turmeric plants is expected to reduce the application of nematicides. This research was conducted on November 2017-February 2018, in Dieng Banjarnegara. The results show the effect of turmeric on intercropping system had not been able to control the cysts population through the eggs, beside that the eggs are not decrease due to genetic factors of each nematode and environment that effect on eggs formation. But the balancing of use turmeric plants on intercropping system could reduce the cysts population. It can be seen on K1P1 (1 Potato : 1 Turmeric) treatment that showed of decreases of cysts population compared to control treatment. The difference on cysts population is caused by turmeric root exudates.